Human Cytomegalovirus Infection Induces Rapamycin-Insensitive Phosphorylation of Downstream Effectors of mTOR Kinase - Kudchodkar, Sagar B. (American Society for Microbiology, 2004)
Signaling mediated by the cellular kinase mammalian target of rapamycin (mTOR) activates cap-dependent translation under normal (nonstressed) conditions. However, translation is inhibited by cellular stress responses or rapamycin treatment, which inhibit mTOR kinase activity. We show that during human cytomegalovirus (HCMV) infection, viral protein synthesis and virus production proceed relatively normally when mTOR kinase activity is inhibited due to hypoxic stress or rapamycin treatment. Using rapamycin inhibition of mTOR, we show that HCMV infection induces phosphorylation of two mTOR effectors, eucaryotic initiation factor 4E (eIF4E) binding protein (4E-BP) and eIF4G. The virally induced phosphorylation of eIF4G is both mTOR and phosphatidylinositol 3-kinase (PI3K) independent, whereas the phosphorylation of 4E-BP is mTOR independent, but PI3K dependent. HCMV infection does not induce mTOR-independent phosphorylation of a third mTOR effector, p70S6 kinase (p70S6K). We show that the HCMV-induced phosphorylation of eIF4G and 4E-BP correlates with the association of eIF4E, the cap binding protein, with eIF4G in the eIF4F translation initiation complex. Thus, HCMV induces mechanisms to maintain the integrity of the eIF4F complex even when mTOR signaling is inhibited.